Not My Problem: Vicarious Conflict Adaptation with Human and Virtual Co-actors - Spapé, Michiel M.; Ravaja, Niklas (Frontiers in Psychology, 2016)
The Simon effect refers to an incompatibility between stimulus and response locations resulting in a conflict situation and, consequently, slower responses. Like other conflict effects, it is commonly reduced after repetitions, suggesting an executive control ability, which flexibly rewires cognitive processing and adapts to conflict. Interestingly, conflict is not necessarily individually defined: the Social Simon effect refers to a scenario where two people who share a task show a conflict effect where a single person does not. Recent studies showed these observations might converge into what could be called vicarious conflict adaptation, with evidence indicating that observing someone else’s conflict may subsequently reduce one’s own. While plausible, there is reason for doubt: both the social aspect of the Simon Effect, and the degree to which executive control accounts for the conflict adaptation effect, have become foci of debate in recent studies. Here, we present two experiments that were designed to test the social dimension of the effect by varying the social relationship between the actor and the co-actor. In Experiment 1, participants performed a conflict task with a virtual co-actor, while the actor-observer relationship was manipulated as a function of the similarity between response modalities. In Experiment 2, the same task was performed both with a virtual and with a human co-actor, while heart-rate measurements were taken to measure the impact of observed conflict on autonomous activity. While both experiments replicated the interpersonal conflict adaptation effects, neither showed evidence of the critical social dimension. We consider the findings as demonstrating that vicarious conflict adaptation does not rely on the social relationship between the actor and co-actor.